2007
DOI: 10.1128/aem.00358-07
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic and Small-Subunit rRNA Analyses Reveal the Genetic Diversity of Bacteria, Archaea, Fungi, and Viruses in Soil

Abstract: Recent studies have highlighted the surprising richness of soil bacterial communities; however, bacteria are not the only microorganisms found in soil. To our knowledge, no study has compared the diversities of the four major microbial taxa, i.e., bacteria, archaea, fungi, and viruses, from an individual soil sample. We used metagenomic and small-subunit RNA-based sequence analysis techniques to compare the estimated richness and evenness of these groups in prairie, desert, and rainforest soils. By grouping se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
324
5
11

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 495 publications
(361 citation statements)
references
References 63 publications
21
324
5
11
Order By: Relevance
“…For example, temperature (Fernández et al, 1998) and humidity (Levetin, 1989(Levetin, , 1990Wu et al, 2004), which change at both seasonal and short-term scales, are positively correlated with fungal spore density. On a smaller scale, sporadic phenomena such as soil disturbances or sporulation events also have an influence on fungal diversity in the air (Lighthart and Stetzenbach, 1994;Madelin, 1994;Fierer et al, 2007). Interestingly, in our study, there is more similarity in fungal diversity in the beginning (A21) and end (M30) of spring compared to our sample in the middle (A28) (Fig.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…For example, temperature (Fernández et al, 1998) and humidity (Levetin, 1989(Levetin, , 1990Wu et al, 2004), which change at both seasonal and short-term scales, are positively correlated with fungal spore density. On a smaller scale, sporadic phenomena such as soil disturbances or sporulation events also have an influence on fungal diversity in the air (Lighthart and Stetzenbach, 1994;Madelin, 1994;Fierer et al, 2007). Interestingly, in our study, there is more similarity in fungal diversity in the beginning (A21) and end (M30) of spring compared to our sample in the middle (A28) (Fig.…”
Section: Discussionmentioning
confidence: 39%
“…Rarefaction curves describe the growth of a number of species discovered as a function of the number of samples. For all of our samples, curves have begun to flatten, which is typical in metagenomic studies (Tringe et al, 2005;Fierer et al, 2007), indicating that representative, unbiased sampling of fungal diversity has been recovered (Fig. 2).…”
Section: Discussionmentioning
confidence: 56%
“…The phylogenetic placement of the archaeal phylotypes represented by these sequences is shown in Figure 1. As only the most abundant archaea were recovered by our method, it should be stressed that the phylogenetic tree represents relationships among the most dominant archaea and does not depict the full extent of archaeal diversity in these soils, which is potentially much greater (Fierer et al, 2007). The majority of the archaeal phylotypes (90.9% of all archaeal sequences) were contained within the group 1.1b crenarchaeotal clade (Jurgens et al, 2000), which has been shown previously to be dominant in soils (Auguet et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…only bacteria), with far less attention paid to unicellular and multicellular eukaryotes despite increasing evidence that the diversity of soil fungi, protists and metazoa is likely far higher than often considered [14][15][16]. Indeed, there are few cross-domain assessments of below-ground diversity (but see [17,18]). Additionally, the vast majority of soil diversity studies have been conducted in natural settings, yet anthropogenic pressures now structure many ecosystems and it remains unclear whether there are consistent processes structuring soil biodiversity and biogeography in natural and urban ecosystems.…”
Section: Introductionmentioning
confidence: 99%